Implementasi Google Sites Pada Pokok Bahasa Dinamika Partikel Untuk Menuntaskan Hasil Belajar Siswa Kelas X MIPA 2 Di MAN 4 Denanyar Jombang - Arrofi'uddin, Muhammad Hilmi; Wulandari, Kartika; Husna, Asiyah Lu'lu'ul (Universitas KH. A. Wahab Hasbullah, 2022)
The 2013 curriculum emphasizes the importance of understanding the structure or important ideas of a discipline, through the active involvement of students in learning. Therefore, students must be thorough in understanding the material before continuing with the next material. This study aims to complete student learning outcomes after learning using google sites learning media on the subject of Particle Dynamics.The design of this research is a One-Shot Case Study. The population referred to in this study is all 38 students of class X MIPA 2 in even semesters at MAN 4 Denanyar Jombang in the academic year 2021/2022. The sample used in this study were 38 students of class X MIPA 2 as many as 38 students. The instrument used in this study was a learning outcome test sheet. Based on the results of the study, it was concluded that the application of google sites learning media on the subject of Particle Dynamics can complete student learning outcomes.